Smart Parenting dalam Mengatasi Social Withdrawal pada Anak di Pondok Pesantren - Hasan Baharun; Madinatul Jennah (Institut Agama Islam Negeri (IAIN) Tulungagung, 2019)
Smart Parenting is a pattern of education strategies for children, where parents as madrasatul ula (the first educators) in nurturing and guiding child development. The principle of Smart Parenting what is good for parents is good for children too. It make no problem in the process of child development such as social withdrawal. Social Withdrawal will arise when children experience stress and feel depressed in their lives. This problem is rampant among children, especially among